Examining the Boundaries of Hate Crime Policy: Considering Age and Gender. (May 2013) - Mason-Bish, Hannah
The emergence of hate crime legislation in Great Britain and the United States has generated public debate and has increasingly been the focus of academic work. Relatively little research has examined how and why certain victim categories might be considered and then dismissed from the hate crime policy domain. Drawing on original qualitative research, this article aims to fill that gap by focusing specifically on the exclusion of age and gender from hate crime policy in Britain by exploring the ways in which decisions are made about the characteristics of hate crime victim groups by policy makers and activists. This article asks important questions about how different forms of violence are conceptualized and understood by practitioners and theorists alike. It also addresses how claims for victims' rights are framed to make changes to the criminal justice system.